1984
DOI: 10.4039/ent11669-1
|View full text |Cite
|
Sign up to set email alerts
|

A STRAIN OF FRUITTREE LEAFROLLER, ARCHIPS ARGYROSPILUS (LEPIDOPTERA: TORTRICIDAE), TOLERANT TO AZINPHOS-METHYL IN AN APPLE ORCHARD REGION OF THE OKANAGAN VALLEY OF BRITISH COLUMBIA

Abstract: Probit analysis of the dosage response of first instar, fruittree leafroller larvae to azinphos-methyl indicated that a strain from a commercial orchard in East Kelowna, B.C. was 7.8 times more tolerant than a susceptible strain. Azinphos-methyl applied to experimental apple blocks in the same area did not provide satisfactory control. Leafroller damage as high as 10.5% was found in several orchards which had received multiple azinphos-methyl and other organophosphorous insecticide treatments. The development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Leafroller control in commercial apple orchards in British Columbia has involved the use of organophosphate insecticides since the 1960s, with diazinon and azinphosmethyl the most widely used (Madsen 1969). Neonate larvae of fruittree leafroller were first reported to be resistant to diazinon in 1977 (Madsen and Carty 1977) and to azinphosmethyl in the early 1980s (Vakenti et al 1984). Cossentine and Jensen (1991) reported that LD 50 values for azinphosmethyl of male A. argyrospila caught in pheromone traps from 1986 to 1988 were similar to those reported by Vakenti et al (1984), and generally reflected the success of control measures in individual orchards.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Leafroller control in commercial apple orchards in British Columbia has involved the use of organophosphate insecticides since the 1960s, with diazinon and azinphosmethyl the most widely used (Madsen 1969). Neonate larvae of fruittree leafroller were first reported to be resistant to diazinon in 1977 (Madsen and Carty 1977) and to azinphosmethyl in the early 1980s (Vakenti et al 1984). Cossentine and Jensen (1991) reported that LD 50 values for azinphosmethyl of male A. argyrospila caught in pheromone traps from 1986 to 1988 were similar to those reported by Vakenti et al (1984), and generally reflected the success of control measures in individual orchards.…”
Section: Introductionmentioning
confidence: 73%
“…Neonate larvae of fruittree leafroller were first reported to be resistant to diazinon in 1977 (Madsen and Carty 1977) and to azinphosmethyl in the early 1980s (Vakenti et al 1984). Cossentine and Jensen (1991) reported that LD 50 values for azinphosmethyl of male A. argyrospila caught in pheromone traps from 1986 to 1988 were similar to those reported by Vakenti et al (1984), and generally reflected the success of control measures in individual orchards. There have not been any reports of resistance in populations of A. rosana, likely because the two sympatric univoltine leafrollers are similar in appearance as larvae, exhibit the same phenology, and are difficult to distinguish accurately without rearing specimens to adulthood.…”
Section: Introductionmentioning
confidence: 73%
“…A. argyrospila has developed resistance to the organophosphate insecticides diazinon (Madsen & Carty, 1977) and azinphosmethyl (Vakenti et al, 1984) in parts of the Okanagan valley. These findings indicate that A. rosana should be more successful in exploiting a wider host range than are A. argyrospila.…”
Section: Discussionmentioning
confidence: 99%
“…A. argyrospila may therefore be the dominant species only under conditions where they have some other biological advantage, such as resistance to insecticides. A. argyrospila has developed resistance to the organophosphate insecticides diazinon (Madsen & Carty, 1977) and azinphosmethyl (Vakenti et al, 1984) in parts of the Okanagan valley. There have been no reports of insecticide resistance in A. rosana or in the two bivoltine species in British Columbia.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical pesticides are effective against the tortrix moths and larvae; however, they also kill non-target beneficial insects, especially the pollinators for J. curcas [ 29 ]. Previously, Bt -derived biological insecticides were used to control tortrix moths Archips argyrospilus (Walker) on apple and pear [ 30 , 31 ] and Archips rosanus (L.) on filberts [ 32 ]. The effectiveness of Bt on the two tortrix moths suggests cry gene may be used to control A. micaceanus on J. curcas plants.…”
Section: Introductionmentioning
confidence: 99%